2010
DOI: 10.1631/jzus.b0900074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moniliformin and selenium on human articular cartilage metabolism and their potential relationships to the pathogenesis of Kashin-Beck disease

Abstract: Abstract:Objective: To investigate the effects of mycotoxin moniliformin (MON) on the metabolism of aggrecan and type II collagen in human chondrocytes in vitro and the relationship between MON and Kashin-Beck disease (KBD). Methods: Human chondrocytes were isolated and cultured on bone matrix gelatin to form an artificial cartilage model in vitro with or without MON toxin. Cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The expression of aggrecan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Similar in vitro effects have also been reported by Zhang et al [18] where an exposure of human fetal chondrocytes for 5 days to MON (1000, 2000, 4000, 8000, 16,000 and 32,000 µg L −1 ) was enough to significantly decrease cell viability. The same authors have shown through immunohistochemistry that MON (4000 µg L −1 ) triggered the expression of MMP-13, and promoted the catabolism of aggrecan and Coll II in human chondrocytes exposed for 16 days.…”
Section: Discussionsupporting
confidence: 87%
“…Similar in vitro effects have also been reported by Zhang et al [18] where an exposure of human fetal chondrocytes for 5 days to MON (1000, 2000, 4000, 8000, 16,000 and 32,000 µg L −1 ) was enough to significantly decrease cell viability. The same authors have shown through immunohistochemistry that MON (4000 µg L −1 ) triggered the expression of MMP-13, and promoted the catabolism of aggrecan and Coll II in human chondrocytes exposed for 16 days.…”
Section: Discussionsupporting
confidence: 87%
“…Zhao et al reported that polysaccharide extracted from selenium-enriched Ganoderma lucidum had a DNAprotective effect against oxidative damage by hydroxyl radicals and that a high selenium concentration had a much stronger effect against hydroxyl and superoxide radicals 30 . In addition, Zhang et al reported that moniliformin toxin promoted the catabolism of aggrecan and type II collagen in cultured human chondrocytes and that selenium could partially alleviate the damage of aggrecan induced by moniliformin toxin 37 . Moreover, in China, endemic selenium deficiency is often accompanied by endemic iodine deficiency; all selenium-deficient areas of China are also areas of iodine deficiency disease 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in the regulation of HSP27 26. CRK can promote cell motility by a Rho and hyaluronan‐CD44‐dependent signaling mechanism 27, and may be relevant in KBD chondrocytes, since increased expression of CD44 has been shown in KBD cartilage 28, and in mycotoxin moniliformin‐affected cartilage 29. Keratin 1 (K2C1) contributes to signal transduction as a signal receptor complex by binding with integrin.…”
Section: Discussionmentioning
confidence: 99%